UPAYA MENINGKATKAN KETERAMPILANMENULIS TEKS DESKRIPSI MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA SISWA KELAS VII-C SMPNEGERI 3 PANCUR BATU TAHUN PELAJARAN 2018/2019 - Yohana Sitohang; Dian Syahfitri; Panigoran Siburian (Jurnal Darma Agung, 2019)
The ability of description text writing is a competency that must be achieved in K.D 4.12. This research aims at improving writing skills by applying discovery learning model on students class VII-C of SMPN 3 Pancur Batu based on the result of classroom action research conducted in 2 cycles.This can be seen from the activities of students in the learning process which increasingly improves in each cycle in the first cycle an average of 63.33% and learning completeness isas many as 36.37% and increasing in the second cycle is obtained by an average of 87.67% and Learning condition is as many as 13.33%. It can be said that cycle II run very good. There has been an increase in the results of the description text writing skills because it gained a significant increase of 63 to 81. In this activity, the students did the followings: (1) observing activities, (2) finding activities, (3) asking activities, (4) trying activities, (5) communication activities. Based on the results of the above assessment conducted by the teacher, including attitude competency assessment with direct observation techniques, knowledge competency assessment with written test techniques in the form of describing an object in the first cycle and then in the second cycle the written test returns a description question.